Representative Metaphor in the holy Quran (A Rhetorical, Descriptive and Analytical Study): فن الاستعارة التمثيلية في القرآن الكريم (دراسة بلاغية تحليلية) - Nazar, Dr. Shabana; Yousaf, Dr. Muhammad Shuaib; Shafiullah, Dr. Hafiz (Al-Aijaz Research Journal of Islamic Studies & Humanities, 2021)
The holy Quran has employed the vatious rhetoric methods in a way that Arabs have never known before so much, so it was unique and miraculous in its style that the holy quran has employed to explain the meaning that would help in the conveyance of the ideas to the mind of the reader. So Many scholars have paid close attention to the literal figuration and emphasized on it in every era to discover and find out the literal and eloquent beauties of the semantic embellishment of the holy Quran. In this research Article the researchers has tried his best to find out the Figurative metaphor and its various types in the holy Quran especially in Sura Hood. The aim of this research is to sort out the Rhetorical embellishments inside the Holy Quran and its impacts on readers of the holy Quran keeping in view the provision of the related examples of with elaborative statements on the occasions.